Integration of AI and OR Techniques in Constraint Programming for Combinatorial Optimization Problems : 10th International Conference, CPAIOR 2013, Yorktown Heights, NY, USA, May 18-22, 2013. Proceedings - Sellmann, Meinolf; Gomes, Carla (Lecture Notes in Computer Science, 2013)
This volume is a compilation of the research program of the 10th International Conference on the Integration of Artificial Intelligence (AI) and Operations Research (OR) Techniques in Constraint Programming, CPAIOR 2013, held at Yorktown Heights, NY, USA, in May 2013. This volume contains 20 full papers and 11 short papers that were carefully reviewed and selected from 71 submissions. The papers focus on new techniques or applications in the intersection of constraint programming (CP), artificial intelligence (AI) and operations research (OR).